(untitled) (مجلة إحالات, 2025)
تهدف هذه الدّراسة إلى كشف تجليات ومظاهر النّزعة الرّمزيّة الّتي عرفتها الرّواية العربيّة المعاصرة، وربطها بمرجعياتها ومصادرها في تراثنا العربيّ والإسلاميّ والعالميّ، من خلال رواية "رمل الماية" للرّوائيّ العربيّ الجزائريّ "واسيني الأعرج"؛ الّتي حاول من خلالها استنطاق التّاريخ المغيَّب والمسكوت عنه في قالب أدبيّ فنيّ رمزيّ، وإجراء محاكمة عادلة لتاريخ الحكّام والسّلاطين المزيّف؛ الّذي كتبه الورّاقون والمؤرخون عنهم، وقد توصّلت هذه الدّراسة -بعد التّطرّق إلى أهم مصادر الرّمز في مدونتها- إلى أنّ هذه الرّواية ثريّة بالعديد من الصّور الرّمزيّة إلى درجة أنّه يمكن أن نحكم عليها أنّها ذات نزعة رمزيّة دون تردّد. Abstract: The purpose of this study is to uncover the manifestations and manifestations of the symbolic tendency that the contemporary Arab narrative has identified, and to link it to its references and sources in our Arab, Islamic and world heritage, Through the novel "sand money" of the novelist Algerian Arab "Wassini Alaraj"; in which he tried to interrogate the history of the hidden and silent in the form of literary and symbolic art, and a fair trial of the history of rulers and sultans fake; This study, after addressing the most important sources of the code in its blog, found that this novel is rich in so many symbolic images that it can be judged without any hesitation. key words: The tendency symbolism, wassini al aradj, the contemporary Arabic novel, raml el maya.